2010
DOI: 10.1002/marc.201000133
|View full text |Cite
|
Sign up to set email alerts
|

Diketopyrrolopyrroles as Acceptor Materials in Organic Photovoltaics

Abstract: In the search of new electron acceptor, n-type materials for organic solar cells that combine a strong absorption over a broad range with good electrical characteristics, the use of diketopyrrolopyrrole (DPP) derivatives with low reduction potentials is explored. A series of small molecule DPP derivatives is presented and the compounds are tested as electron acceptors in combination with poly(3-hexylthiophene) (P3HT) as the donor material. Working photovoltaic devices are obtained that show a photoresponse in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 24 publications
0
70
0
4
Order By: Relevance
“…[13] Unlike Perkins mauveine, Pechmann dyes never became commercial, and after the 1950s became virtually forgotten to a large extent due to the intractable nature of these highly insoluble materials. [10-12, 14, 15] We recognised the similarities of the Pechmann lactams III and such popular organic semiconductor building blocks as N,N-dialkyldipyrollopyrollediones [16] (DPP) and N,N-dialkylnaphthalene-1,8:4,5-tetracarboxydiimides [17,18] (NDI). All of these chromophores have planar, conjugated rings that are highly prone to p-p stacking and carry carboxyl/anhydride functionality that allows facile amidation or imidation; the choice of the alkyl amine dictates the solubility, aggregation and solid-state packing and has a profound influence on organic thin-film transistor (OTFT) and organic photovoltaic (OPV) devices manufactured from organic semiconducting materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] Unlike Perkins mauveine, Pechmann dyes never became commercial, and after the 1950s became virtually forgotten to a large extent due to the intractable nature of these highly insoluble materials. [10-12, 14, 15] We recognised the similarities of the Pechmann lactams III and such popular organic semiconductor building blocks as N,N-dialkyldipyrollopyrollediones [16] (DPP) and N,N-dialkylnaphthalene-1,8:4,5-tetracarboxydiimides [17,18] (NDI). All of these chromophores have planar, conjugated rings that are highly prone to p-p stacking and carry carboxyl/anhydride functionality that allows facile amidation or imidation; the choice of the alkyl amine dictates the solubility, aggregation and solid-state packing and has a profound influence on organic thin-film transistor (OTFT) and organic photovoltaic (OPV) devices manufactured from organic semiconducting materials.…”
Section: Introductionmentioning
confidence: 99%
“…Polymers derived from compounds 5-8 at the 5-position of the thiophene rings would thus be structurally similar to P3HT but would have a higher degree of planarity that could, in principle, facilitate good electron/hole transport through the polymer backbone. For analogous polymers derived from Pechmann lactams, poly(thiophene-DPP) [16] and poly(thiophene-NDI) [17] derivatives would be more appropriate structures to compare. B3LYP/DGDZVP modelling showed that the lowest-energy conformation of model thiophene-DPP and thiophene-NDI monomers ( Figure 1, Ar = 2-thienyl, R = isobutyl; the isobutyl group is a realistic model for the long, branched 2-(alkyl 1 )alkyl 2 chains such as 2-octyldodecyl that are attached to the N atoms in order to solubilise actual polymers synthesised and tested in the laboratory) are characterised by thiophene-core dihedral angles of 14 and 648, respectively.…”
mentioning
confidence: 99%
“…[1] For example, in the case of organic light-emitting diodes,n -type materials play an important role in electron injection and hole blockingt oe nsure that exciton formation occurs in the emitting layer. [1] For example, in the case of organic light-emitting diodes,n -type materials play an important role in electron injection and hole blockingt oe nsure that exciton formation occurs in the emitting layer.…”
Section: Introductionmentioning
confidence: 99%
“…Explanations for this can be found in the fact that the electrochemical experiment takes place in solution, where stacking of the molecules is absent, resulting in a higher bandgap. 57 However, E g CV is relatively lower compared with E g opt (1.69 eV) in solution, We think that the result have relation to the test concentration in the different environment. Interestingly, the insertion of the phenylene group between DPP-2T and dicyanovinyl moiety, instead of thiophene, resulted in an ~0 .14 eV drop for LUMO and E g compared with those of the previously reported thiophene analogue (LUMO = -3.68 eV, E g CV = 1.69 eV).…”
Section: Photophysical Properties and Homo/lumo Energiesmentioning
confidence: 84%